Innovations for Sustainable Infrastructure – Experience from Azerbaijan Rural Investment Project (AZRIP) - Post, David; Ishihara, Satoshi (World Bank, Washington, DC, 2012)
Over the past decade plus, Community Driven Development (CDD) has proven to be an effective strategy for promoting the development of small-scale infrastructure. Indeed, by involving community members in decision-making processes and project implementation, the CDD approach increases community ownership of investments projects and enhances their sustainability. However, despite its successes in the realm of small scale infrastructure, CDD's track record in promoting sustainability for more complex infrastructure projects (such as roads and water supply systems) is mixed at best and the connection between community ownership and sustainable infrastructure is not well established for larger scale projects. In order to ensure that the 'triple bottom line' of sustainable infrastructure is met in the context of CDD operations, infrastructure investments need to be selected and implemented using an integrated approach that combines sound economics, solid engineering and attention to social dynamics and environmental sustainability. By successfully incorporating a variety of innovations, the Azerbaijan Rural Investment Project (AZRIP) demonstrates how adopting a comprehensive approach, including a focus on life-cycle costs, private sector participation, and participatory processes, is critical for achieving sustainable infrastructure investments. As such, AZRIP serves as a good example of how close engagement with communities and attention to sustainability in project design and implementation can lead to positive development outcomes and the achievement of the 'triple bottom line'.